16k-13k-(-5k)+12k+(-19k)=-19

Simple and best practice solution for 16k-13k-(-5k)+12k+(-19k)=-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16k-13k-(-5k)+12k+(-19k)=-19 equation:



16k-13k-(-5k)+12k+(-19k)=-19
We move all terms to the left:
16k-13k-(-5k)+12k+(-19k)-(-19)=0
We add all the numbers together, and all the variables
15k-(-5k)+(-19k)+19=0
We get rid of parentheses
15k+5k-19k+19=0
We add all the numbers together, and all the variables
k+19=0
We move all terms containing k to the left, all other terms to the right
k=-19

You can always share this solution

See similar equations:

| ?7/9(x+3)=14 | | 20=56x | | 3n+9n+(-3n)-13n=16 | | 2x+5=47-7x | | 3n+9n+-3n-13n=16 | | 0.5(x-4)=5 | | 14+5x=(-x+3)-1 | | 6(x+1)=3-x | | 20a+-17a+-5a=-8 | | -0.8(10-x)=36 | | 18w-18w+5w-4w=15 | | 3xx5=9 | | 3(q+45)=-3 | | 4x-4x=16-16 | | 101+5x-9+2x+11=180 | | 27=3(t-70) | | 0=-9(d-92) | | 2x-18+79+x-16=180 | | 13x–4=52+5x | | 0.4(x-7)=18 | | 2z-7=-3 | | 3x+12=92–7x | | b+5/5=10 | | 12^3p+8+10=97 | | 8x+8=2+14x | | 2-2b=14 | | -3d+-16=-1 | | 13=2d-3 | | 2(2x-16)=7(x-23) | | 45b-5.25b+3=3.75 | | 5^x-3=25^x-3 |

Equations solver categories